Organizacyjne i ekonomiczne aspekty fuzji i przejęć przedsiębiorstw oraz ich wpływ na stosowane systemy zarządzania - Białowąs, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The author describes the possible method of a merger of entities according to Polish law. The article shows the main problems connected with a stage after the marger. It is the problem of computer of computer systems, ISO standards, various culture etc. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 179-185